Pemberdayaan Perpustakaan Desa melalui Implementasi Gerakan Nasional Gemar Membaca di Kecamatan Suwawa Kabupaten Bone Bolango - Malabar, Sayama; Salam, Salam; Lantowa, Jafar (Jurnal Sibermas (Sinergi Pemberdayaan Masyarakat), 2019)
The Village Project Program –Independent Campus aims to empower libraries by implementing the national reading movement. This program is implemented through education and training, mentoring, service, and guidance, which are expected to be sustainable through the awareness of related parties, especially the government and regional libraries. These parties are expected to pay attention to village library facilities and infrastructure that can realize the national reading movement program.Besides, to support the national reading movement, the program is also directed at forming literacy communities, literacy lodges, and reading parks in Bone Bolango.The Freedom to Learn - Independent Campus Community Service Program with the theme "Empowerment of Village Libraries through the Implementation of the National Reading Movement" is implemented by prioritizing the principle of empowering local communities with the primary objective of program sustainability and public awareness of the importance of literacy. Therefore, after the Freedomto Learn – Independent Campus Community Service Program is completed, the community, especially the Youth Organization, can continue the program that has been run independently through the Subdistrict Literacy Community forum.Villages need to empower their assets both in terms of human resources and management of the sources of funds used. The focus of empowerment is to improve the community's quality in the literacy skills sector and a better institutional administration system in encouraging the development of reading culture programs.Reading culture in the village can make people have the ability to read from the start and encourage them to love reading. It is recommended for students who take part in Community Service Program in the following years to further improve communication with the community in order to make it easier to run the programs implemented in Tinelo, Bubeya, and Boludawa village